What makes a chronic pelvic pain patient satisfied? - Jenna N. Wygant; Lois J. McGuire; Nicole M. Bush; Tatnai L. Burnett; Isabel C. Green; Daniel M. Breitkopf (Taylor & Francis Group, 2019)
Purpose: Caring for women with chronic pelvic pain (CPP) is challenging. There have been few studies on what factors patients consider to be important when being treated for their pelvic pain. This study sought to identify the key factors of the health care visit that contribute to patient's overall satisfaction with their care in a CPP clinic. Materials and methods: Between January 2015 and December 2016, new patients visiting a tertiary care CPP clinic were recruited to complete a patient satisfaction survey. Inductive thematic analysis was performed on response data regarding important factors that impact patient satisfaction with their visit/care. Results: Five themes of patient satisfaction identified included: providers with a compassionate and caring attitude, being listened to, clear communication with collaboration when needed, quality time spent with patient, and having a plan of care with recommendations. The theme regarding provider's compassion and listening skills was the most frequently identified. Pain relief was seldom mentioned as a source of patient satisfaction. Conclusions: The data suggest that a focus on empathic communication may make a meaningful difference in meeting the needs of women with CPP as well as strengthening the provider/patient relationship.